2020
DOI: 10.1080/08897077.2019.1635955
|View full text |Cite
|
Sign up to set email alerts
|

Friends and Relatives as Sources of Prescription Opioids for Misuse among Young Adults: The Significance of Physician Source and Race/Ethnic Differences

Abstract: Background: Given the public health issues associated with prescription opioid misuse, there is surprisingly little research on sources of prescription opioids for misuse. We know that free from friends/relatives is the most common source, that source is associated with patterns of misuse, and that sources vary based on the sociodemographic characteristics. The current research assesses how friends/relatives obtain the prescription opioids they freely share with others.Methods: Data were from the 2009-2014 Nat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…Recent research on young adults suggests that when the friend or family member’s source (ie, the source for the person who gives the respondent medication for free) is from a purchase or from multiple sources, odds of other substance use problems in the respondent are also elevated. 83 Having a family member on long-term opioid therapy increases odds of longer post-surgical use in adolescents and young adults, 163 and having a family member with any opioid prescription increases the likelihood of developing an opioid use disorder. 164 Finally, Rigg and colleagues 84 examined a local, southeastern Pennsylvania sample of adults 20 to 62 years and found that the pattern of sources at the initial opioid misuse episode differed from the past-year pattern in respondents, with somewhat higher rates of obtaining from a friend or family member and of purchases from a dealer at the later assessment.…”
Section: Prescription Opioid Misuse Across the Lifespanmentioning
confidence: 99%
“…Recent research on young adults suggests that when the friend or family member’s source (ie, the source for the person who gives the respondent medication for free) is from a purchase or from multiple sources, odds of other substance use problems in the respondent are also elevated. 83 Having a family member on long-term opioid therapy increases odds of longer post-surgical use in adolescents and young adults, 163 and having a family member with any opioid prescription increases the likelihood of developing an opioid use disorder. 164 Finally, Rigg and colleagues 84 examined a local, southeastern Pennsylvania sample of adults 20 to 62 years and found that the pattern of sources at the initial opioid misuse episode differed from the past-year pattern in respondents, with somewhat higher rates of obtaining from a friend or family member and of purchases from a dealer at the later assessment.…”
Section: Prescription Opioid Misuse Across the Lifespanmentioning
confidence: 99%
“…In addition to correlates and sociodemographic differences, medication sources for PDM (Ford et al, 2020) and PDM motives (Blevins et al, 2017; Drazdowski et al, 2020) have been examined in young adults. As noted in a review by Hulme et al (2018), the primary medication source for young adult college students is from peers or family.…”
mentioning
confidence: 99%
“…Knowing the sources from which misusers obtained their supply of prescription medicine will be useful as tackling the sources and drug diversions may be a preventive measures that can help reduce this problem. Studies in the west 46,47 have shown that misusers obtained their supply from a multitude of sources (e.g. doctor-hopping, friends, families, drug dealers) and understanding the nuances of drug diversions in these cases will help policy makers draft policy to address the sources and drug diversions to prevent prescription medicine misuse from evolving into a major healthcare issue in this region.…”
Section: Discussionmentioning
confidence: 99%